Tinjauan Terhadap Bagi Hasil Perikanan Pada Tradisi Huyula Di Wilayah Pesisir Pantai Paguat (International Forum of Researchers and Lecturers, 2023)
This research aims to find out an overview of fisheries profit sharing in the Huyula Tradition in the Paguat Coastal Area, based on the title raised in this research. This research uses a type of normative legal research. The process of collecting data from the objects studied in this research is using library research. The data obtained by this research uses a normative analysis method, namely by interpreting and discussing research material based on law, legal norms, legal theories and doctrines related to the main problem. The results of this research show that the Juridical Review of Fishery Profit Sharing in the Huyula Tradition on the Paguat Coast, namely in the Bongoime Village community, Huyula values are applied by the community in various aspects of life. Huyula values are manifested in various activities, for example in community service for environmental cleanup rural areas, building village roads, death, cleaning local irrigation canals and agricultural activities. Community service activities for the public interest, in coordination with the local government without distinguishing between social status, community service activities are usually referred to as